Analisis Perbandingan Return dan Risk antara Saham Syariah dengan Saham Konvensional (Studi pada Saham Syariah di Jakarta Islamic Index dan Saham Konvensional di Investor 33 Periode 2020-2022) - Alfu Alfi Ni'am; Diah Syifaul A'yuni (AL-UJRAH, 2024)
In the era of globalization, investment has become a long-term strategy to achieve financial well-being and independence. Technological advancements have facilitated access to various investment instruments, including the Islamic capital market that offers investment options aligned with Islamic economic principles. This study employs a quantitative descriptive method to analyze the comparison of returns and risks between sharia stocks in the Jakarta Islamic Index and conventional stocks in the Investor33 Index during the 2020-2022 period. Quantitative analysis is used to test hypotheses, while descriptive analysis illustrates the collected data. Results show that the average return for sharia stocks is 1.06% and for conventional stocks is 1.61%, while the average risk for sharia stocks is 11.56% and for conventional stocks is 11.59%. The independent sample t-test yields significance values (2-tailed) of 0.372 for return and 0.491 for risk, both greater than 0.05. This indicates no significant difference in either return or risk between sharia and conventional stocks during the study period.